2016
DOI: 10.1016/j.nutres.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Twice weekly intake of farmed Atlantic salmon (Salmo salar) positively influences lipoprotein concentration and particle size in overweight men and women

Abstract: The US Dietary Guidelines for Americans recommend twice weekly fish intake. Farmed Atlantic salmon is a good source of omega-3 (n-3) fatty acids which have positive lipid modifying effects; however, it is unknown whether these responses are dose-dependent. Our primary research objective was to determine the effect of dose-dependent intake of farmed Atlantic salmon on lipoprotein particle (P) size and concentration. We hypothesized that low-density lipoprotein (LDL)-P and high-density lipoprotein (HDL)-P size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…As an example, omega-3-fatty acids raise LDL cholesterol via increases in particle size, but may be beneficial for cardiovascular health. 31 , 32 Determination of apoB and apoC3 levels may shed light on this question. Another possibility for the small increases in cholesterol relates to the known function of SIRT1 in promoting reverse cholesterol transport from cells.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, omega-3-fatty acids raise LDL cholesterol via increases in particle size, but may be beneficial for cardiovascular health. 31 , 32 Determination of apoB and apoC3 levels may shed light on this question. Another possibility for the small increases in cholesterol relates to the known function of SIRT1 in promoting reverse cholesterol transport from cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our studies, there are only three previous trials investigating the effect of fish intake using NMR lipoprotein data. In these studies, high fish intake had no significant effect on HDL particle size . However, these studies had small sample sizes and in two of these studies the fish consumed was either partly or entirely lean fish .…”
Section: Discussionmentioning
confidence: 91%
“…There are only a few intervention studies that have examined the effect of fish intake on lipoprotein subclasses, especially in individuals at high risk of developing CVD . In these studies, fish intake has been reported to decrease the size and concentrations VLDL particles and increase the size and concentrations of HDL particles and lipid components in the particles as compared with control diets.…”
Section: Introductionmentioning
confidence: 99%
“…Marine oils have exhibited strong cardioprotective properties as has been extensively reviewed [ 24 ]. Thus, several dietary guidelines (i.e., The US Dietary Guidelines) and healthy dietary patterns (i.e., the Mediterranean diet) recommend fish intake at least twice weekly [ 3 , 11 , 25 ]. Intake of farmed Atlantic salmon twice weekly influences lipoprotein particle size, decreases serum concentrations of triglycerides, and increases HDL cholesterol in a manner associated with CVD risk reduction [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%